Sistem Pengendalian Suhu Air Nutrisi Hidroponik NFT (Nutrient Film Tehnique) Menggunakan Sensor Suhu Dan Sms Gateway Berbasis Arduino (Studi Kasus Di Siliwangi Indah Hidroponik) - Nurul Khabib Allin (Elkom : Jurnal Elektronika dan Komputer, 2019)
Hydroponics are now increasingly in demand, should be checked regularly so that hydroponic plants thrive. Likewise, in Siliwangi Indah Hydroponics Semarang, which still uses manual methods, namely the absence of a device that detects nutrient water temperature and pH automatically and the absence of tools that can normalize nutrients automatically. Arduino Uno R3 can be used to detect temperature automatically with a temperature sensor DS18B20, and detect pH with a pH sensor. Then the sensor readings are sent to the farmer's cellphone with SMS Gateway. The sensor readings are also used to divert the flow of nutrients from the spare reservoir, so that the nutrients remain normal. So this tool can automatically measure the nutrient water temperature and pH and replace the main nutrients to the reserve nutrients. And the assessment obtained from experts on this tool gets a value of 3.6 and from the expert gets a value of 3.7. Hydroponic nutrition in this study is maintained normally and farmers always know the nutritional state. So that the hydroponic plants thrive and have maximum yields.